Report for the year 1908-09 on the financial condition of Denmark with a survey of the estimates for 1909-10 and 1910-11 : presented to both Houses of Parliament by command of His Majesty, February, 1910 - Grande-Bretagne. Foreign Office
Antériorité : "Reference to previous report, annual series no. 4211"